Bibliometric Analysis on Islamic and Conventional Money Demand - Ramadhini, Fiona; Irfany, Mohammad Iqbal (SMART Insight, 2023)
The Islamic finance industry in the world has been snowballing in the last ten years. In its implementation, the Islamic financial system does not use an interest rate system but uses a profit-sharing system. The increase in global Islamic financial assets is in line with the theory that states that the profit-sharing system is better than the interest system because the Islamic money demand model, which uses the profit-sharing system, tends to be more resistant to shocks compared to the conventional money demand model which uses the interest system. This research aims to prove the validity of this theory. By using the method of bibliometric, the author found 391 studies that discussed